Employee Trust in Supervisors and Affective Commitment: The Moderating Role of Authentic Leadership. Issue 3 (June 2016) - Xiong, Kehan; Lin, Weipeng; Li, Jenny C.; Wang, Lei
Although previous research has examined the main/direct effects of subordinates' trust in their supervisors on the levels of subordinates' affective commitment towards the organizations, little attention has been paid to explore the boundary conditions of this relationship. Two studies were conducted to examine the moderating effect of authentic leadership on the relationship between subordinates' trust in supervisor and their levels of affective commitment towards the organization. In line with the hypothesized model, both Study 1 (cross-sectional design, n  = 138) and Study 2 (lagged design, n  = 154) demonstrated that authentic leadership moderated the relationship between employees' trust in supervisor and their levels of affective commitment towards their organizations. Specifically, the positive relationship was stronger for employees under higher levels of authentic leadership. The implications for theory and practice are discussed.